Numerical investigation of the impact of wall boundaries on aerodynamic noise in high-speed trains - Zhi-Yuan Ma; Qingsong Feng; Prasert Prapamonthon; Gong Cheng; Zhen-xu Sun; Dilong Guo; Guo-Wei Yang (Engineering Applications of Computational Fluid Mechanics, 2026)
As the operating speed of high-speed trains continues to rise, aerodynamic noise has become a critical factor influencing train performance and passenger comfort, especially in confined environments like tunnels. In this study, a comprehensive simulation of the aerodynamic noise generated during the entire ‘open air-tunnel-open air’ transition at 450 km/h was performed using the improved delayed detached eddy simulation (IDDES) turbulence model and overset grid method, with results validated against field measurements. The findings reveal that, compared to open-air conditions, the tunnel environment induces higher-flow velocities around the train, stronger pressure fluctuations on the train surface, and more pronounced vortex shedding in the wake. Sound pressure levels (SPLs) at surface measurement points are typically about 10 dB(A) higher in the tunnel, with the primary differences observed in the 100–300 Hz frequency range, while both scenarios exhibit spectral peaks near 530 Hz. In the bogie region, tunnel noise is dominated by pressure-wave coupling and wall reflections, which amplify low- and mid-frequency components, whereas under open-air conditions, local vortex shedding and wake instabilities prevail, resulting in more high-frequency noise. The web structure contributes to the reduction of aerodynamic noise from the bogie area, with a particularly significant decrease observed in tunnel conditions. Along the tunnel wall, the SPL initially increases and then decreases, reaching a peak of 125.7 dB(A). After exiting the tunnel, the measurement points at Section L in the open air show a reduction of approximately 10 dB(A) compared to the corresponding tunnel-wall points. This study highlights the substantial amplification of low-frequency noise caused by wall confinement and demonstrates the noise-reduction potential of the web structure. The results provide valuable theoretical insights and numerical evidence for aerodynamic noise control in higher-speed train tunnels, offering significant engineering implications.
Keywords: Aerodynamics and Fluid Dynamics Research; Railway Engineering and Dynamics; Fluid Dynamics and Vibration Analysis